THE RELATIONSHIP BETWEEN SMOKING AND QUALITY OF LIFE IN BRONCHIAL ASTHMA PATIENTS - Marlin Sutrisna; Siska Lestari; Elsi Rahmadani (STIKES Syedza Saintika Padang, 2021)
ABSTRACT Bronchial asthma represents 1.8% of the total global disease. It is estimated that 346,000 deaths worldwide each year are due to bronchial asthma. The purpose of this study was to determine the relationship between smoking and the quality of life of bronchial asthma patients. The method used is descriptive with a cross sectional approach. The population in this study were all bronchial asthma patients at the Puller Health Center in Mukomuko Regency in 2020. The sampling technique used a purposive sampling technique, a total sample of 46 people. This study uses the chi-square test. The results of the univariate test analysis showed that most of the respondents (58.6%) with bronchial asthma smoked and most of the respondents (58.7%) with bronchial asthma had a poor quality of life. While the bivariate analysis test found that there was a relationship between smoking and quality of life in bronchial asthma patients. It is suggested to the puskesmas to be able to improve education in bronchial asthma patients to provide counseling to patients regarding several factors that cause a decrease in the patient's quality of life. Keywords : Bronchial Asthma ; Quality of Life ; Smoke